WRITTEN CORRECTIVE FEEDBACK: STUDENTS’ PERCEPTION ON ONLINE LEARNING - Larasati Nur Yuliawati; Bambang Harmanto; Diyah Atiek Mustikawati; Ana Maghfiroh (PROJECT (Professional Journal of English Education), 2021)
WCF from the lecturer is useful information for student writing improvement. It aids students in identifying their English learning problems and skills. Students, on the other hand, may interpret lecturer WCF differently than the lecturer intended. This study is aimed at describing the type of lecturer’s WCF and the students’ perception of lecturer’s WCF in a paragraph writing class. It is descriptive qualitative research, employing documentation and interview as research instruments, which was conducted with 18 students of the third semester English department students of Muhammadiyah University of Ponorogo. Furthermore, there were five out of 18 students randomly selected to be interviewed to discover students’ perspective of the given feedback. The findings revealed that, firstly, the lecturer use praise, criticism, and suggestion based on students task in paragraph writing class. Secondly, students’ positive responses of having feedback and the benefit of written corrective feedback that students get. Finally, most students responded that they appreciated the lecturer’s WCF. In addition, the students believed that lecturer’s WCF could improve student’s writing especially on grammar accuracy and organization, and it could motivate the student in developing the ideas. Keywords:  Student’s Perspective, Written Corrective Feedback, Writing